การสำรวจปัจจัยที่ผู้สมัครเลือกเรียนที่โรงเรียนสอนอาหารครัววันดี A SURVEY OF STUDENTS APPLYING FACTORS AT WANDEE CULINARY ART SCHOOL - ณ สงขลา ศรียาภัย, วิชุดา; กุโลภาส, ธีรภัทร (An Online Journal of Education, 2018)
Abstract This study was a survey research aiming to study the decision making factors for the applicants who enrolled the courses at Wandee Culinary Art School. The sample for this research consists of the applicants who enrolled any courses at Wandee Culinary Art School during March – May 2016 for 50 persons. Questionnaires were used to collect data using five rating scale. All data were analyzed by frequency, mean, and standard deviation. The research findings for the decision factors the applicants choose to study at Wandee Culinary Art School the most in order as follows: 1) course and teaching methodology 2) school reputation 3) ease to commute 4) school building 5) the facilities and welfare 6) valuable experience from the school 7) self-competent and interest in cookery. The applicants at Wandee Culinary Art School are mostly female, got bachelor degree, apply the course without prior visit, and know the school via Internet. The majority have their own business, earn more than 50,000 THB a month